GAYA HIDUP KOMUNITAS MUSIK METAL GRIEF BLOZZOM DI KOTA PEKANBARU - Sitompul, Itscan; ', Yesi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
Heavy metal is a genre of music with fast beats and guitar sounds with distortion effects coupled with scream vocals that seem loud and aggressive. The way of dressing and the symbols used by musicians and metal music fans have their own uniqueness which is considered to deviate from local understanding and culture which is thick with the value of modesty. This research aims to identify and analyze the lifestyle and symbols of the Grief Blozzom heavy metal music community in Pekanbaru city. This research uses qualitative research methods. Data collection was carried out in this study in the form of direct observation, in-depth interviews, and documentation. The results of this study indicate that the Grief Blozzom metal music community in Pekanbaru city in its activities are involved in podcasts, sharing sessions, meetings between members and concerts to gain knowledge capital, social capital, economic and symbolic capital. In the use of their free time, members of the Grief Blozzom heavy metal music community use their free time by exploring and listening to heavy metal music and hanging out to increase their knowledge capital and social capital. The finger symbol means the identity of the band concept which is manifested through the use of the finger symbol. Merchandise worn by heavy metal music fans means the identity of the metal music subgenre they like and a form of pride as a heavy metal music fan. Dance in enjoying heavy metal music is interpreted as communication between the audience and musicians to get each other more excited in the dance. Dance becomes a form of pride when able to move people with their music. Keywords: Lifestyle, Heavy Metal, Community, Pekanbaru, Symbols